2012
DOI: 10.1159/000336574
|View full text |Cite
|
Sign up to set email alerts
|

Early Enteral Nutrition Reduces the Rate of Life-Threatening Complications after Thoracic Esophagectomy in Patients with Esophageal Cancer

Abstract: Background: Early postoperative enteral nutrition has been suggested to improve the nutritional status of patients after esophageal surgery. However, whether enteral nutrition decreases rates of surgical complications and increases the completion rate of the clinical management pathway is unclear. Methods: We analyzed 154 patients who were randomly assigned to either an enteral or parenteral nutrition group after undergoing esophagectomy, compared the incidence of surgical complications, and evaluated the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 43 publications
2
62
1
3
Order By: Relevance
“…Following esophagectomy, early initiation of enteral nutrition is preferred over parenteral nutrition because it has been proven to reduce the number of life-threatening complications and length of hospital stay [78][79][80]. Enteral nutrition can be administered via tube feeding, by a surgically placed jejunostomy or a nasoduodenal or jejunal tube, or via oral intake.…”
Section: Initiation Of Nutritionmentioning
confidence: 99%
“…Following esophagectomy, early initiation of enteral nutrition is preferred over parenteral nutrition because it has been proven to reduce the number of life-threatening complications and length of hospital stay [78][79][80]. Enteral nutrition can be administered via tube feeding, by a surgically placed jejunostomy or a nasoduodenal or jejunal tube, or via oral intake.…”
Section: Initiation Of Nutritionmentioning
confidence: 99%
“…20,21 In our department patients who underwent an esophagectomy were given enteral nutrition on POD 1, which made it easier for them to maintain the balance and made it possible to remove the chest tube early. 22 In order to obtain satisfactory results, we now routinely use the new volume threshold instead of traditional management for postoperative chest tube removal after TSE.…”
Section: Thoracoscopic Esophagectomy: Early Chest Tube Removalmentioning
confidence: 99%
“…Studies have shown that the use of enteral nutrition after surgery can effectively reduce the incidence of postoperative pulmonary infections (27,29). Earlier use is more effective at reducing the postoperative pulmonary infection incidence (30,31 In principle, enteral nutrition should be preferentially used for patients with a normal digestive tract. Parenteral nutrition supplements should be administered when enteral nutrition is insufficient.…”
Section: Treatmentmentioning
confidence: 99%